Pengembangan Media Crossword Puzzle pada Pembelajaran Biologi Kelas X - Agustina Agustina; Yunita Wardianti; Sepriyaningsih Sepriyaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the validity, practicality, and effectiveness of Crossword Puzzle Media in Biology Learning for Class X of SMA Negeri 8 Lubuklinggau. This research method uses the research and development method (Research and Development) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The results of the study showed that the validation analysis of the crossword puzzle media obtained a value from linguists of 4.29, media experts of 4.86, and material experts of 4.86 which indicates that the crossword puzzle media developed meets the valid criteria with an average score of 4.67. Meanwhile, the results of the practicality sheet analysis obtained a value of 96% from educators, 86.66% in the one-to-one test and 91.33% in the small group test which shows that the crossword puzzle media meets the practical criteria with an average percentage of 91.33%. In the field trial, an N-Gain of 0.74 was obtained with a high classification. In conclusion, the crossword puzzle media has proven valid, practical, and effective in improving learning outcomes in biology learning for 10th graders at SMA Negeri 8 Lubuklinggau. Keywords: ADDIE, Crossword Puzzle, Biology, Learning Media